CNTNAP2 intracellular domain (CICD) generated by γ-secretase cleavage improves autism-related behaviors - Jing Zhang; Fang Cai; Renbin Lu; Xiaoliang Xing; Lu Xu; Kunyang Wu; Zishan Gong; Qing Zhang; Yun Zhang; Mengen Xing; Weihong Song; Jia-Da Li (Signal Transduction and Targeted Therapy, 2023)
Abstract As the most prevalent neurodevelopmental disorders in children, autism spectrum disorders (ASD) are characterized by deficits in language development, social interaction, and repetitive behaviors or inflexible interests. Contactin associated protein like 2 (CNTNAP2), encoding a single transmembrane protein (CNTNAP2) with 1331 amino acid residues, is a widely validated ASD-susceptible gene. Cntnap2-deficient mice also show core autism-relevant behaviors, including the social deficits and repetitive behavior. However, the cellular mechanisms underlying dysfunction CNTNAP2 and ASD remain elusive. In this study, we found a motif within the transmembrane domain of CNTNAP2 was highly homologous to the γ-secretase cleavage site of amyloid-β precursor protein (APP), suggesting that CNTNAP2 may undergo proteolytic cleavage. Further biochemical analysis indicated that CNTNAP2 is cleaved by γ-secretase to produce the CNTNAP2 intracellular domain (CICD). Virally delivery of CICD to the medial prefrontal cortex (mPFC) in Cntnap2-deficient (Cntnap2 −/− ) mice normalized the deficit in the ASD-related behaviors, including social deficit and repetitive behaviors. Furthermore, CICD promoted the nuclear translocation of calcium/calmodulin-dependent serine protein kinase (CASK) to regulate the transcription of genes, such as Prader Willi syndrome gene Necdin. Whereas Necdin deficiency led to reduced social interaction in mice, virally expression of Necdin in the mPFC normalized the deficit in social preference of Cntnap2 −/− mice. Our results thus reveal a critical function of CICD and highlight a role of the CNTNAP2-CASK-Necdin signaling pathway in ASD.